Rare earth element doped lithium germanium phosphorus sulfur solid electrolyte and its preparation method and application
By doping rare earth elements into lithium germanium phosphorus and sulfur solid electrolytes, the safety hazards and low ion conductivity of traditional lithium-ion batteries are solved, and a higher battery circulation capacity and energy density are achieved.
Patent Information
- Application Number
- CN202310227223.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-09
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-03-09
AI Technical Summary
Traditional lithium-ion batteries use organic liquid electrolytes with safety risks, and the ionic conductivity of solid electrolytes is low, which limits the improvement of battery energy density.
By doping rare earth elements in the lithium germanium phosphorus and sulfur solid electrolyte, replacing part of the germanium element, the distribution and concentration of lithium ions are adjusted and its ionic conductivity is improved.
The ionic conductivity of lithium germanium phosphorus and sulfur solid electrolyte is significantly improved, the jump rate and conductivity of lithium ions are enhanced, the grain boundary resistance is reduced, and the circulation capacity and energy density of the battery are improved.
Smart Images

Figure CN116190773B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a rare earth element-doped lithium germanium phosphorus sulfur solid electrolyte and a preparation method and application thereof. Background Art
[0002] Since the lithium-ion battery was launched in the 1990s, it has gradually become an important energy storage device in modern life. Due to its advantages such as high energy density, high output power, low self-discharge, no memory effect, and environmental friendliness, lithium-ion batteries are widely used in daily life and various fields from rail transportation to the production of electronic products. However, conventional lithium-ion batteries use organic liquid electrolytes as ion transport media. These organic liquid electrolytes have various safety hazards such as leakage, volatilization, and combustion. Side reactions with electrodes during charging and discharging can lead to a decrease in battery capacity and service life. Since the lithium-ion battery was launched in the 1990s, it has gradually become an important energy storage device in modern life. Due to its advantages such as high energy density, high output power, low self-discharge, no memory effect, and environmental friendliness, lithium-ion batteries are widely used in daily life and various fields from rail transportation to the production of electronic products. However, conventional lithium-ion batteries use organic liquid electrolytes as ion transport media. These organic liquid electrolytes have various safety hazards such as leakage, volatilization, and combustion. Side reactions with electrodes during charging and discharging can lead to a decrease in battery capacity and service life.
[0003] In addition, the electrolyte and the membrane occupy a large part of the volume and mass of traditional lithium-ion batteries, which limits the increase in battery energy density. When the liquid electrolyte is replaced with a solid electrolyte, the safety issues caused by the electrolyte will be solved. Through special assembly technology, the electrodes and the electrolyte membrane can be stacked in the same mold to form a battery internal series, which is of great significance to improve the energy density of the entire battery module. In addition, the energy density of traditional lithium-ion batteries using graphite anodes is close to its upper limit. The next generation of high-energy-density batteries represented by the lithium metal system are difficult to adapt to the electrolyte environment, because the uneven lithium deposition on the surface of the lithium anode during operation can easily lead to the growth of lithium dendrites, piercing the membrane, causing short circuits or explosions. In addition, the use of solid electrolytes can alleviate the above problems, which also brings possibilities for the development and use of solid-state lithium metal batteries.
[0004] Solid electrolytes have high mechanical strength and a wide electrochemical window, which can meet the application requirements of high-voltage cathodes and high-metal lithium anodes at the same time, which is of great significance to improving the energy density of lithium batteries. All-solid-state lithium batteries are considered to be the next-generation lithium battery technology with great development potential due to their advantages of high energy density and high safety. As the core component of solid-state lithium batteries, solid electrolytes directly affect the performance of batteries, such as energy density, cycle stability, and working safety. In recent years, various strategies have been adopted to improve the performance of electrolytes. However, the research and application of electrolytes still face many existing problems. The main problem is the basic electrochemical properties of electrolytes, such as ionic conductivity and lithium ion transfer number. Higher ionic conductivity and lithium ion transfer number can reduce the polarization of the battery and guide the uniform deposition of lithium ions. These are the most basic requirements.
[0005] Thirty years ago, solid-state lithium-ion batteries lost out in the competition with organic electrolyte lithium-ion batteries due to the relatively low ionic conductivity of solid electrolytes. In recent years, significant progress has been made in improving the ionic conductivity of solid electrolytes. 10 GeP2S 12 (LGPS) was developed, and its ionic electrolyte is higher than liquid electrolyte (2.5×10 -2 Scm -1 ), with high thermal stability and high energy density. Although its lithium ion conductivity can reach the level of commercial liquid electrolytes, its cost is relatively high, and its application in sulfide solid electrolytes has yet to be studied. Therefore, it is necessary to explore a solid electrolyte material with high ion conductivity and good chemical stability. Summary of the invention
[0006] The embodiment of the present invention provides a rare earth element doped lithium germanium phosphorus sulfur solid electrolyte and its preparation method and application, wherein lithium sulfide Li2S, germanium sulfide GeS2, sulfide of rare earth element M, and phosphorus pentoxide P2S5 are synthesized by a high temperature solid phase method, wherein the lithium sulfide Li2S is in an excess of 5%-10%; the valence state of the rare earth element is positive trivalent, and the tetravalent germanium element in the lithium germanium phosphorus sulfur solid electrolyte is partially replaced by doping, and the vacancies in the lattice of the lithium germanium phosphorus sulfur solid electrolyte are compensated by lithium ions. The optimal lithium ion concentration is adjusted by substitution doping of unequal cations, which can significantly increase the number of lithium ion transfers, change the distribution of lithium ions, increase the lithium ion hopping rate, and reduce the grain boundary resistance, thereby improving the ionic conductivity of the lithium germanium phosphorus sulfur solid electrolyte.
[0007] The invention achieves the purpose of reducing the cost of electrolyte and improving the lithium ion conductivity and lithium metal stability by replacing Ge with rare earth elements.
[0008] In a first aspect, an embodiment of the present invention provides a rare earth element doped lithium germanium phosphorus sulfur solid electrolyte, wherein the rare earth element doped lithium germanium phosphorus sulfur solid electrolyte has a chemical formula of Li 10+x Ge 1-x M x P2S 12 , wherein 0.01≤x<1, M includes: one or more rare earth elements selected from lanthanum La, cerium Ce, praseodymium Pr, neodymium Nd, promethium Pm, samarium Sm, europium Eu, gadolinium Gd, terbium Tb, dysprosium Dy, holmium Ho, erbium Er, thulium Tm, ytterbium Yb, lutetium Lu, scandium Sc, and yttrium Y;
[0009] The rare earth element has a positive trivalent valence, and is doped to replace a portion of the positive tetravalent Ge element in the lithium germanium phosphorus sulfur solid electrolyte. The vacancies in the crystal lattice of the lithium germanium phosphorus sulfur solid electrolyte are replaced by Li + to make compensation;
[0010] The rare earth element doped lithium germanium phosphorus sulfur solid electrolyte is prepared by synthesizing lithium sulfide Li2S, germanium sulfide GeS2, sulfide of the rare earth element M, and phosphorus pentoxide P2S5, wherein the amount of lithium sulfide Li2S added is 5%-10% excess according to the stoichiometric ratio.
[0011] In a second aspect, an embodiment of the present invention provides a method for preparing the rare earth element-doped lithium germanium phosphorus-sulfur solid electrolyte described in the first aspect, the preparation method comprising:
[0012] Step S1, weighing raw materials according to a stoichiometric ratio: lithium sulfide Li2S, germanium sulfide GeS2, sulfide of rare earth element M and phosphorus pentoxide P2S5; placing the raw materials in a grinder, adding a first dispersant under a protective atmosphere, grinding and mixing evenly to obtain a mixed material;
[0013] Step S2, placing the mixed material in a ball mill, performing the first ball milling under a protective atmosphere, and placing the material in a vacuum drying oven for drying to evaporate the dispersant to obtain a powder;
[0014] Step S3, loading the powder into a corundum crucible, placing the crucible in a vacuum atmosphere furnace, evacuating the vacuum, and then filling the crucible with an inert gas for pre-sintering to obtain a pre-sintered bulk material;
[0015] Step S4, placing the pre-sintered bulk material in a ball mill, adding a second dispersant, and performing a second ball milling to obtain a precursor material;
[0016] Step S5, placing the precursor material in a vacuum atmosphere furnace, evacuating the vacuum and then filling it with an inert gas to perform a high-temperature solid-phase reaction, naturally cooling to room temperature after the reaction is completed, and performing a third ball milling after the material is discharged to obtain a rare earth element-doped lithium germanium phosphorus sulfur solid electrolyte;
[0017] The chemical formula of the rare earth element doped lithium germanium phosphorus sulfur solid electrolyte is Li 10+x Ge 1-x M x P2S 12 , wherein 0.01≤x<1, M includes: one or more rare earth elements selected from lanthanum La, cerium Ce, praseodymium Pr, neodymium Nd, promethium Pm, samarium Sm, europium Eu, gadolinium Gd, terbium Tb, dysprosium Dy, holmium Ho, erbium Er, thulium Tm, ytterbium Yb, lutetium Lu, scandium Sc, and yttrium Y;
[0018] The amount of lithium sulfide Li2S added is 5%-10% excess according to the stoichiometric ratio.
[0019] Preferably, the sulfide of the rare earth element M includes one or more of the rare earth element sulfides of lanthanum La, cerium Ce, praseodymium Pr, neodymium Nd, promethium Pm, samarium Sm, europium Eu, gadolinium Gd, terbium Tb, dysprosium Dy, holmium Ho, erbium Er, thulium Tm, ytterbium Yb, lutetium Lu, scandium Sc, and yttrium Y;
[0020] The first dispersant includes: one or more of deionized water, anhydrous ethanol, propanol, and ethylene glycol; the mass ratio of the first dispersant to the total mass of the raw materials is 1:[0.8-1.5];
[0021] The second dispersant includes: one or more of deionized water, anhydrous ethanol, propanol, and ethylene glycol; the mass ratio of the second dispersant to the pre-burned block material is 1:[0.8-1.5].
[0022] Preferably, the protective atmosphere is nitrogen atmosphere and / or argon atmosphere;
[0023] The inert gases are nitrogen and / or argon.
[0024] Preferably, the first ball milling and the second ball milling are both wet milling processes, the ball milling speed is 550 rpm-750 rpm, and the ball milling time is 10 hours-20 hours;
[0025] The third ball milling is a dry milling process, the ball milling speed is 600 rpm, and the ball milling time is 2 hours.
[0026] Preferably, the drying temperature is 80°C-200°C, and the drying time is 2 hours-6 hours;
[0027] The temperature of the pre-sintering treatment is 200° C.-300° C., and the time of the pre-sintering treatment is 10 hours-15 hours.
[0028] Preferably, the temperature of the high-temperature solid-phase reaction is 500° C.-600° C., the heating rate is 2° C. / min-4° C. / min, and the time of the high-temperature solid-phase reaction is 10 hours-20 hours.
[0029] In a third aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the rare earth element-doped lithium-germanium-phosphorus-sulfur solid electrolyte described in the first aspect.
[0030] The embodiment of the present invention provides a rare earth element doped lithium germanium phosphorus sulfur solid electrolyte and its preparation method and application, wherein lithium sulfide Li2S, germanium sulfide GeS2, sulfide of rare earth element M and phosphorus pentoxide P2O5 are synthesized by a high temperature solid phase method, wherein the lithium sulfide Li2S is in an excess of 5%-10%; the valence state of the rare earth element is positive trivalent, and the positive tetravalent germanium element in the lithium germanium phosphorus sulfur solid electrolyte is doped to replace part of the lithium germanium phosphorus sulfur solid electrolyte, and the vacancies in the lattice of the lithium germanium phosphorus sulfur solid electrolyte are compensated by lithium ions, and the optimal lithium ion concentration is adjusted by substitution doping of unequal cations, which can significantly increase the number of lithium ion transfers, change the distribution of lithium ions, increase the lithium ion hopping rate, reduce the grain boundary resistance, and thus improve the ionic conductivity of the lithium germanium phosphorus sulfur solid electrolyte; the rare earth element doped lithium germanium phosphorus sulfur solid electrolyte provided by the embodiment of the present invention is applied to an all-solid-state lithium secondary battery to improve its cycle capacity.
[0031] A rare earth element-doped lithium germanium phosphorus-sulfur solid electrolyte provided in an embodiment of the present invention reduces the manufacturing cost of the electrolyte by selecting rare earth resources with abundant reserves and relatively low prices to dope and replace part of the germanium element; a rare earth element-doped lithium germanium phosphorus-sulfur solid electrolyte preparation method provided in an embodiment of the present invention is environmentally friendly, energy-saving, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0033] Figure 1 It is a flow chart of a method for preparing a rare earth element-doped lithium-germanium-phosphorus-sulfur solid electrolyte provided by an embodiment of the present invention;
[0034] Figure 2 It is the X-ray diffraction (XRD) diagram of the rare earth element doped lithium germanium phosphorus sulfur solid electrolyte provided in Examples 1-5 of the present invention. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0036] The embodiment of the present invention provides a rare earth element doped lithium germanium phosphorus sulfur solid electrolyte, the chemical formula of the rare earth element doped lithium germanium phosphorus sulfur solid electrolyte is Li 10+x Ge 1-x M x P2S 12 , wherein 0.01≤x<1, M includes: one or more rare earth elements selected from lanthanum La, cerium Ce, praseodymium Pr, neodymium Nd, promethium Pm, samarium Sm, europium Eu, gadolinium Gd, terbium Tb, dysprosium Dy, holmium Ho, erbium Er, thulium Tm, ytterbium Yb, lutetium Lu, scandium Sc, and yttrium Y;
[0037] The valence state of rare earth elements is positive trivalent, and they are doped to replace part of the positive tetravalent Ge element in the lithium germanium phosphorus sulfur solid electrolyte. The vacancies in the lattice of the lithium germanium phosphorus sulfur solid electrolyte are replaced by Li + to make compensation;
[0038] The rare earth element doped lithium germanium phosphorus sulfur solid electrolyte is prepared by synthesizing lithium sulfide Li2S, germanium sulfide GeS2, sulfide of rare earth element M, and phosphorus pentoxide P2S5, wherein the amount of lithium sulfide Li2S added is 5%-10% excess according to the stoichiometric ratio.
[0039] The present invention provides a method for preparing the rare earth element doped lithium germanium phosphorus sulfur solid electrolyte. Figure 1 As shown, the specific steps include:
[0040] Step S1, weighing raw materials according to a stoichiometric ratio: lithium sulfide Li2S, germanium sulfide GeS2, sulfide of rare earth element M and phosphorus pentoxide P2S5; placing the raw materials in a grinder, adding a first dispersant under a protective atmosphere, grinding and mixing them evenly to obtain a mixed material;
[0041] Wherein, the added amount of lithium sulfide Li2S is 5%-10% excess according to the stoichiometric ratio.
[0042] The sulfide of the rare earth element M includes one or more of the rare earth element sulfides containing lanthanum La, cerium Ce, praseodymium Pr, neodymium Nd, promethium Pm, samarium Sm, europium Eu, gadolinium Gd, terbium Tb, dysprosium Dy, holmium Ho, erbium Er, thulium Tm, ytterbium Yb, lutetium Lu, scandium Sc, and yttrium Y;
[0043] The first dispersant includes: one or more of deionized water, anhydrous ethanol, propanol, and ethylene glycol; the mass ratio of the first dispersant to the total mass of the raw materials is 1:[0.8-1.5];
[0044] The protective atmosphere is a nitrogen atmosphere and / or an argon atmosphere.
[0045] Step S2, placing the mixed material in a ball mill, performing the first ball milling under a protective atmosphere, and placing the material in a vacuum drying oven for drying to evaporate the dispersant to obtain a powder;
[0046] The first ball milling is a wet milling process, the ball milling speed is 550 rpm-750 rpm, and the ball milling time is 10 hours-20 hours;
[0047] The drying temperature is 80°C to 200°C, and the drying time is 2 hours to 6 hours.
[0048] Step S3, loading the powder into a corundum crucible, placing the crucible in a vacuum atmosphere furnace, evacuating the vacuum, and then filling the crucible with an inert gas for pre-sintering to obtain a pre-sintered bulk material;
[0049] Wherein, the inert gas is nitrogen and / or argon;
[0050] The temperature of the pre-sintering treatment is 200° C.-300° C., and the time of the pre-sintering treatment is 10 hours-15 hours.
[0051] Step S4, placing the pre-sintered bulk material in a ball mill, adding a second dispersant, and performing a second ball milling to obtain a precursor material;
[0052] The second dispersant includes one or more of deionized water, anhydrous ethanol, propanol, and ethylene glycol; the mass ratio of the second dispersant to the pre-burned block material is 1:[0.8-1.5];
[0053] The second ball milling is a wet milling process, the ball milling speed is 550rpm-750rpm, and the ball milling time is 10 hours-20 hours.
[0054] Step S5, placing the precursor material in a vacuum atmosphere furnace, evacuating the vacuum and then filling it with an inert gas to perform a high-temperature solid-phase reaction, naturally cooling to room temperature after the reaction is completed, and performing a third ball milling after the material is discharged to obtain a rare earth element-doped lithium germanium phosphorus sulfur solid electrolyte;
[0055] Wherein, the inert gases are nitrogen and / or argon;
[0056] The third ball milling was a dry milling process, the ball milling speed was 600 rpm, and the ball milling time was 2 hours.
[0057] The temperature of the high-temperature solid-phase reaction is 500°C-600°C, the heating rate is 2°C / min-4°C / min, and the time of the high-temperature solid-phase reaction is 10 hours-20 hours.
[0058] In this application, the amount of lithium sulfide Li2S is added according to the stoichiometric ratio of 105%-110%. Excessive Li2S can increase the Li +The concentration and fluidity of the material are improved, thereby improving the ionic conductivity of the material. The positive trivalent rare earth elements are closer to the tetravalent Ge in terms of atomic radius, and can provide lattice vacancies to the greatest extent without changing the purity of the main phase, thereby providing Li + It provides channels for the flow of ions, further improving the ionic conductivity of the material.
[0059] The embodiment of the present invention provides a use of a rare earth element-doped lithium germanium phosphorus sulfur solid electrolyte prepared by the above-mentioned preparation method. The rare earth element-doped lithium germanium phosphorus sulfur solid electrolyte can be used as a positive electrode additive, a negative electrode additive, a diaphragm coating material additive, a diaphragm coating material or a solid-state battery electrolyte of a lithium ion battery.
[0060] In order to better understand the technical solution provided by the present invention, the preparation process of the rare earth element-doped lithium-germanium-phosphorus-sulfur solid electrolyte of the present invention is respectively described below with specific examples.
[0061] Example 1
[0062] This embodiment provides a preparation method and performance test of a rare earth element doped lithium germanium phosphorus sulfur solid electrolyte, and the specific preparation steps are as follows:
[0063] Step S1, press Li 10.1 Ge 0.9 Eu 0.1 P2S 12 The raw materials are weighed in a stoichiometric ratio: 540 g of lithium sulfide Li2S, 90 g of germanium sulfide GeS2, 5 g of europium sulfide Eu2S3 and 100 g of phosphorus pentoxide P2S5; the raw materials are placed in a grinder, and 930 g of deionized water is added under a nitrogen atmosphere. After grinding and mixing evenly, a mixed material is obtained, in which the amount of lithium sulfide Li2S added is 7% excess according to the stoichiometric ratio.
[0064] Step S2, placing the mixed material in a ball mill, and performing the first ball milling at a rotation speed of 600 rpm under a nitrogen atmosphere for 10 hours. After the material is discharged, it is placed in a vacuum drying oven at 100° C. for 3 hours to evaporate the dispersant to obtain a powder.
[0065] Step S3, the powder is loaded into a corundum crucible, placed in a vacuum atmosphere furnace, evacuated and then filled with inert gas nitrogen, and pre-fired at 200° C. for 15 hours to obtain a pre-fired block material.
[0066] Step S4, placing the pre-sintered bulk material in a ball mill, adding 930 g of deionized water, and performing a second ball milling at a speed of 600 rpm for 10 hours to obtain a precursor material.
[0067] Step S5, placing the precursor material in a vacuum atmosphere furnace, evacuating the vacuum and then filling it with inert gas nitrogen, heating it to 500°C at a heating rate of 2°C / min, and performing a high-temperature solid-phase reaction for 10 hours. After the reaction is completed, it is naturally cooled to room temperature, and after the material is discharged, it is ball-milled for the third time at a speed of 600 rpm for 2 hours to obtain a rare earth element europium-doped lithium germanium phosphorus sulfur solid electrolyte.
[0068] The XRD pattern of the rare earth element europium-doped lithium germanium phosphorus sulfur solid electrolyte prepared in this embodiment is as follows: Figure 2 As shown, it can be seen that all characteristic diffraction peaks of the lithium germanium phosphorus sulfur solid electrolyte doped with the rare earth element europium are consistent with the characteristic peaks of the lithium germanium phosphorus sulfur solid electrolyte of the standard card PDF#29-0831, and there are no impurity peaks, indicating that the europium doped in the lithium germanium phosphorus sulfur solid electrolyte material doped with the rare earth element europium of the present invention does not affect the pure phase structure of the germanium phosphorus sulfur solid electrolyte itself. This is because the ionic radius of the trivalent rare earth element Eu is close to that of the tetravalent Ge, and doping substitution will not change the purity of the main phase.
[0069] Example 2
[0070] This embodiment provides a preparation method and performance test of a rare earth element doped lithium germanium phosphorus sulfur solid electrolyte, and the specific preparation steps are as follows:
[0071] Step S1, press Li 10.1 Ge 0.9 G 0.1 P2S 12 The raw materials are weighed in a stoichiometric ratio: 545 g of lithium sulfide Li2S, 90 g of germanium sulfide GeS2, 5 g of gadolinium sulfide Gd2S3 and 100 g of phosphorus pentoxide P2S5; the raw materials are placed in a grinder, and 950 g of deionized water is added under a nitrogen atmosphere. After grinding and mixing evenly, a mixed material is obtained, wherein the amount of lithium sulfide Li2S added is 8% excess according to the stoichiometric ratio.
[0072] Step S2, placing the mixed material in a ball mill, and performing the first ball milling at a rotation speed of 600 rpm under a nitrogen atmosphere for 10 hours. After the material is discharged, it is placed in a vacuum drying oven at 100° C. for 3.5 hours to evaporate the dispersant to obtain a powder.
[0073] Step S3, the powder is loaded into a corundum crucible, placed in a vacuum atmosphere furnace, evacuated and then filled with inert gas nitrogen, and pre-fired at 300° C. for 10 hours to obtain a pre-fired block material.
[0074] Step S4, placing the pre-sintered bulk material in a ball mill, adding 950 g of deionized water, and performing a second ball milling at a rotation speed of 550 rpm for 13 hours to obtain a precursor material.
[0075] Step S5, placing the precursor material in a vacuum atmosphere furnace, evacuating the vacuum and then filling it with inert gas nitrogen, heating it to 600° C. at a heating rate of 4° C. / min, and performing a high-temperature solid-phase reaction for 12 hours. After the reaction is completed, it is naturally cooled to room temperature, and after the material is discharged, it is ball-milled for the third time at a speed of 600 rpm for 2 hours to obtain a rare earth element gadolinium-doped lithium germanium phosphorus sulfur solid electrolyte.
[0076] The XRD pattern of the rare earth element gadolinium-doped lithium germanium phosphorus sulfur solid electrolyte prepared in this example is as follows: Figure 2 As shown, it can be seen that all characteristic diffraction peaks of the rare earth element gadolinium-doped lithium germanium phosphorus sulfur solid electrolyte are consistent with the characteristic peaks of the standard card PDF#29-0831, and there are no impurity peaks, indicating that the gadolinium doped in the rare earth element gadolinium-doped lithium germanium phosphorus sulfur solid electrolyte material of the present invention does not affect the pure phase structure of the germanium phosphorus sulfur solid electrolyte itself. This is because the ion radius of the trivalent rare earth element Gd is close to that of the tetravalent Ge, and doping substitution will not change the purity of the main phase.
[0077] Example 3
[0078] This embodiment provides a preparation method and performance test of a rare earth element doped lithium germanium phosphorus sulfur solid electrolyte, and the specific preparation steps are as follows:
[0079] Step S1, press Li 10.1 Ge 0.9 Tb 0.1 P2S 12 The raw materials are weighed in a stoichiometric ratio: 530 g of lithium sulfide Li2S, 90 g of germanium sulfide GeS2, 5 g of terbium sulfide Tb2S3 and 100 g of phosphorus pentoxide P2S5; the raw materials are placed in a grinder, and 1000 g of anhydrous ethanol is added under a nitrogen atmosphere. After grinding and mixing evenly, a mixed material is obtained, wherein the amount of lithium sulfide Li2S added is 5% excess according to the stoichiometric ratio.
[0080] Step S2, placing the mixed material in a ball mill, and performing the first ball milling at a rotation speed of 600 rpm under a nitrogen atmosphere for 10 hours. After the material is discharged, it is placed in a vacuum drying oven at 80° C. and dried for 6 hours to evaporate the dispersant to obtain a powder.
[0081] Step S3, the powder is loaded into a corundum crucible, placed in a vacuum atmosphere furnace, evacuated and then filled with inert gas nitrogen, and pre-fired at 200° C. for 15 hours to obtain a pre-fired block material.
[0082] Step S4, placing the pre-sintered bulk material in a ball mill, adding 1000 g of anhydrous ethanol, and performing a second ball milling at a rotation speed of 600 rpm for 10 hours to obtain a precursor material.
[0083] Step S5, placing the precursor material in a vacuum atmosphere furnace, evacuating the vacuum and then filling it with inert gas nitrogen, heating it to 500°C at a heating rate of 2°C / min, and performing a high-temperature solid-phase reaction for 16 hours. After the reaction is completed, it is naturally cooled to room temperature, and after the material is discharged, it is ball-milled for the third time at a speed of 600 rpm for 2 hours to obtain a rare earth element terbium-doped lithium germanium phosphorus sulfur solid electrolyte.
[0084] The XRD pattern of the rare earth element terbium-doped lithium germanium phosphorus sulfur solid electrolyte prepared in this embodiment is as follows: Figure 2 As shown, it can be seen that all characteristic diffraction peaks of the rare earth element terbium-doped lithium germanium phosphorus sulfur solid electrolyte are consistent with the characteristic peaks of the standard card PDF#29-0831, and there are no impurity peaks, indicating that the terbium doped in the rare earth element terbium-doped lithium germanium phosphorus sulfur solid electrolyte material of the present invention does not affect the pure phase structure of the germanium phosphorus sulfur solid electrolyte itself. This is because the ionic radius of the trivalent rare earth element Tb is close to that of the tetravalent Ge, and doping substitution will not change the purity of the main phase.
[0085] Example 4
[0086] This embodiment provides a preparation method and performance test of a rare earth element doped lithium germanium phosphorus sulfur solid electrolyte, and the specific preparation steps are as follows:
[0087] Step S1, press Li 10.1 Ge 0.9 Dy 0.1 P2S 12 The raw materials are weighed in a stoichiometric ratio: 540 g of lithium sulfide Li2S, 90 g of germanium sulfide GeS2, 5 g of dysprosium sulfide Dy2S3 and 100 g of phosphorus pentoxide P2S5; the raw materials are placed in a grinder, and 930 g of propanol is added under a nitrogen atmosphere. After grinding and mixing evenly, a mixed material is obtained, in which the amount of lithium sulfide Li2S added is 7% excess according to the stoichiometric ratio.
[0088] Step S2, placing the mixed material in a ball mill, and performing the first ball milling at a rotation speed of 600 rpm under a nitrogen atmosphere for 10 hours. After the material is discharged, it is placed in a vacuum drying oven at 90° C. and dried for 4 hours to evaporate the dispersant to obtain a powder.
[0089] Step S3, the powder is loaded into a corundum crucible, placed in a vacuum atmosphere furnace, evacuated and then filled with inert gas nitrogen, and pre-fired at 200° C. for 15 hours to obtain a pre-fired block material.
[0090] Step S4, placing the pre-sintered block material in a ball mill, adding 930 g of propanol, and performing a second ball milling at a rotation speed of 750 rpm for 10 hours to obtain a precursor material.
[0091] Step S5, placing the precursor material in a vacuum atmosphere furnace, evacuating the vacuum and then filling it with inert gas nitrogen, heating it to 550°C at a heating rate of 2°C / min, carrying out a high-temperature solid-phase reaction for 11 hours, and naturally cooling it to room temperature after the reaction is completed. After discharging the material, it is ball-milled for the third time at a speed of 600 rpm for 2 hours to obtain a lithium-germanium-phosphorus-sulfur solid electrolyte doped with the rare earth element dysprosium. This is because the ionic radius of the trivalent rare earth element Dy is close to that of the tetravalent Ge, and doping substitution will not change the purity of the main phase.
[0092] The XRD pattern of the rare earth element dysprosium-doped lithium germanium phosphorus sulfur solid electrolyte prepared in this embodiment is as follows: Figure 2 As shown, it can be seen that all characteristic diffraction peaks of the rare earth element dysprosium-doped lithium germanium phosphorus sulfur solid electrolyte are consistent with the characteristic peaks of the standard card PDF#29-0831, and there are no impurity peaks, indicating that the dysprosium doped in the rare earth element dysprosium-doped lithium germanium phosphorus sulfur solid electrolyte material of the present invention does not affect the pure phase structure of the germanium phosphorus sulfur solid electrolyte itself.
[0093] Example 5
[0094] This embodiment provides a preparation method and performance test of a rare earth element doped lithium germanium phosphorus sulfur solid electrolyte, and the specific preparation steps are as follows:
[0095] Step S1, press Li 10.1 Ge 0.9 Lu 0.1 P2S 12 The raw materials are weighed in a stoichiometric ratio: 556 g of lithium sulfide Li2S, 90 g of germanium sulfide GeS2, 5 g of lutetium sulfide Lu2S3 and 100 g of phosphorus pentoxide P2S5; the raw materials are placed in a grinder, and 800 g of ethylene glycol is added under an argon atmosphere. After grinding and mixing, a mixed material is obtained, in which the amount of lithium sulfide Li2S added is 10% excess according to the stoichiometric ratio.
[0096] Step S2, placing the mixed material in a ball mill, and performing the first ball milling at a rotation speed of 750 rpm under an argon atmosphere for 12 hours. After the material is discharged, it is placed in a vacuum drying oven at 200° C. for 5 hours to evaporate the dispersant to obtain a powder.
[0097] Step S3, the powder is loaded into a corundum crucible, placed in a vacuum atmosphere furnace, evacuated and then filled with inert gas argon, and pre-fired at 200° C. for 15 hours to obtain a pre-fired block material.
[0098] Step S4, placing the pre-sintered block material in a ball mill, adding 800 g of ethylene glycol under an argon atmosphere, and performing a second ball milling at a rotation speed of 750 rpm for 12 hours to obtain a precursor material.
[0099] Step S5, placing the precursor material in a vacuum atmosphere furnace, evacuating the vacuum and then filling it with inert gas argon, heating it to 600°C at a heating rate of 4°C / min, and performing a high-temperature solid-phase reaction for 15 hours. After the reaction is completed, it is naturally cooled to room temperature, and after the material is discharged, it is ball-milled for the third time at a speed of 600 rpm for 2 hours to obtain a rare earth element lutetium-doped lithium germanium phosphorus sulfur solid electrolyte.
[0100] The XRD pattern of the rare earth element lutetium-doped lithium germanium phosphorus sulfur solid electrolyte prepared in this example is as follows: Figure 2 As shown, it can be seen that all characteristic diffraction peaks of the rare earth element lutetium-doped lithium germanium phosphorus sulfur solid electrolyte are consistent with the characteristic peaks of the standard card PDF#29-0831, and there are no impurity peaks, indicating that the lutetium doped in the rare earth element lutetium-doped lithium germanium phosphorus sulfur solid electrolyte material of the present invention does not affect the pure phase structure of the germanium phosphorus sulfur solid electrolyte itself. This is because the ionic radius of the trivalent rare earth element Lu is close to that of the tetravalent Ge, and doping substitution will not change the purity of the main phase
[0101] Example 6
[0102] This embodiment provides a preparation method and performance test of a rare earth element doped lithium germanium phosphorus sulfur solid electrolyte, and the specific preparation steps are as follows:
[0103] Step S1, press Li 10.1 Ge 0.9 Yb 0.1 P2S 12 The raw materials are weighed in a stoichiometric ratio: 530 g of lithium sulfide Li2S, 90 g of germanium sulfide GeS2, 5 g of ytterbium sulfide Yb2S3 and 100 g of phosphorus pentoxide P2S5; the raw materials are placed in a grinder, and 1000 g of anhydrous ethanol is added under a nitrogen atmosphere. After grinding and mixing, a mixed material is obtained, in which the amount of lithium sulfide Li2S added is 5% excess according to the stoichiometric ratio.
[0104] Step S2, placing the mixed material in a ball mill, and performing the first ball milling at a rotation speed of 600 rpm under a nitrogen atmosphere for 10 hours. After the material is discharged, it is placed in a vacuum drying oven at 80° C. and dried for 6 hours to evaporate the dispersant to obtain a powder.
[0105] Step S3, the powder is loaded into a corundum crucible, placed in a vacuum atmosphere furnace, evacuated and then filled with inert gas nitrogen, and pre-fired at 200° C. for 15 hours to obtain a pre-fired block material.
[0106] Step S4, placing the pre-sintered bulk material in a ball mill, adding 1000 g of anhydrous ethanol, and performing a second ball milling at a rotation speed of 600 rpm for 10 hours to obtain a precursor material.
[0107] Step S5, placing the precursor material in a vacuum atmosphere furnace, evacuating the vacuum and then filling it with inert gas nitrogen, heating it to 500°C at a heating rate of 2°C / min, and performing a high-temperature solid-phase reaction for 16 hours. After the reaction is completed, it is naturally cooled to room temperature, and after the material is discharged, it is ball-milled for the third time at a speed of 600 rpm for 2 hours to obtain a rare earth element ytterbium-doped lithium germanium phosphorus sulfur solid electrolyte.
[0108] The XRD pattern of the rare earth element ytterbium-doped lithium germanium phosphorus sulfur solid electrolyte prepared in this embodiment is as follows: Figure 2 As shown, it can be seen that all characteristic diffraction peaks of the rare earth element ytterbium-doped lithium germanium phosphorus sulfur solid electrolyte are consistent with the characteristic peaks of the standard card PDF#29-0831, and there are no impurity peaks, indicating that the ytterbium doped in the rare earth element ytterbium-doped lithium germanium phosphorus sulfur solid electrolyte material of the present invention does not affect the pure phase structure of the germanium phosphorus sulfur solid electrolyte itself. This is because the ionic radius of the trivalent rare earth element Yb is close to that of the tetravalent Ge, and doping substitution will not change the purity of the main phase.
[0109] Example 7
[0110] This embodiment provides a preparation method and performance test of a rare earth element doped lithium germanium phosphorus sulfur solid electrolyte, and the specific preparation steps are as follows:
[0111] Step S1, press Li 10.1 Ge 0.8 Eu 0.1 Tb 0.1 P2S 12 The raw materials are weighed in a stoichiometric ratio: 530 g of lithium sulfide Li2S, 80 g of germanium sulfide GeS2, 5 g of europium sulfide Eu2S3, 5 g of terbium sulfide Tb2S3 and 100 g of phosphorus pentoxide P2S5; the raw materials are placed in a grinder, and 1000 g of anhydrous ethanol is added under a nitrogen atmosphere. After grinding and mixing, a mixed material is obtained, in which the amount of lithium sulfide Li2S added is 5% excess according to the stoichiometric ratio.
[0112] Step S2, placing the mixed material in a ball mill, and performing the first ball milling at a rotation speed of 600 rpm under a nitrogen atmosphere for 10 hours. After the material is discharged, it is placed in a vacuum drying oven at 80° C. and dried for 6 hours to evaporate the dispersant to obtain a powder.
[0113] Step S3, the powder is loaded into a corundum crucible, placed in a vacuum atmosphere furnace, evacuated and then filled with inert gas nitrogen, and pre-fired at 200° C. for 15 hours to obtain a pre-fired block material.
[0114] Step S4, placing the pre-sintered bulk material in a ball mill, adding 1000 g of anhydrous ethanol, and performing a second ball milling at a rotation speed of 600 rpm for 10 hours to obtain a precursor material.
[0115] Step S5, placing the precursor material in a vacuum atmosphere furnace, evacuating the vacuum and then filling it with inert gas nitrogen, heating it to 500°C at a heating rate of 2°C / min, and performing a high-temperature solid-phase reaction for 16 hours. After the reaction is completed, it is naturally cooled to room temperature, and after the material is discharged, it is ball-milled for the third time at a speed of 600 rpm for 2 hours to obtain a lithium-germanium-phosphorus-sulfur solid electrolyte co-doped with rare earth elements terbium and europium.
[0116] The XRD pattern of the lithium germanium phosphorus sulfur solid electrolyte doped with rare earth elements terbium and europium prepared in this embodiment is as follows: Figure 2 As shown, it can be seen that all characteristic diffraction peaks of the lithium germanium phosphorus sulfur solid electrolyte doped with rare earth elements terbium and europium are consistent with the characteristic peaks of the standard card PDF#29-0831, and there are no impurity peaks, indicating that the terbium and europium doped in the lithium germanium phosphorus sulfur solid electrolyte material doped with rare earth elements terbium and europium of the present invention do not affect the pure phase structure of the germanium phosphorus sulfur solid electrolyte itself. This is because the ionic radius of the trivalent rare earth elements Eu and Tb is close to that of the tetravalent Ge, and doping substitution will not change the purity of the main phase.
[0117] In order to better illustrate the effect of the embodiment of the present invention, comparative example 1 is compared with the above embodiment.
[0118] Comparative Example 1
[0119] This comparative example provides a lithium germanium phosphorus sulfur solid electrolyte Li without any doping 10 GeP2S 12 The specific preparation steps of the preparation method and performance test are as follows:
[0120] Step S1, press Li 10 GeP2S 12 The raw materials are weighed in a stoichiometric ratio: 500 g of lithium sulfide Li2S, 100 g of germanium sulfide GeS2 and 100 g of phosphorus pentoxide P2S5, the raw materials are placed in a grinder, 930 g of deionized water is added under a nitrogen atmosphere, and after grinding and mixing evenly, a mixed material is obtained, and then a first ball milling is performed, and the mixture is dried in a vacuum drying oven to evaporate the dispersant solvent to obtain a precursor of a lithium germanium phosphorus sulfur solid electrolyte;
[0121] In this comparative example, only the raw materials weighed in step S1 are different from those in Example 1, and the other steps S2-S5 are the same as those in Example 1. Finally, a lithium germanium phosphorus-sulfur solid electrolyte Li 10 GeP2S 12 .
[0122] The XRD pattern of the lithium germanium phosphorus sulfur solid electrolyte prepared in this comparative example is as follows: Figure 2 As shown, it can be seen that all characteristic diffraction peaks of the lithium germanium phosphorus sulfur solid electrolyte are consistent with the characteristic peaks of the standard card PDF#29-0831, without any impurity peaks.
[0123] Lithium-ion all-solid-state batteries were assembled and tested using the rare earth element-doped lithium-germanium-phosphorus-sulfur solid electrolytes prepared in Examples 1-7 and the lithium-germanium-phosphorus-sulfur solid electrolyte of Comparative Example 1. The assembled batteries used metallic lithium electrodes as negative electrode materials and metal sulfide materials as positive electrode materials, and were assembled using conventional methods.
[0124] The ionic conductivity of the rare earth element doped lithium germanium phosphorus sulfur solid electrolytes of Examples 1-7 and the lithium germanium phosphorus sulfur solid electrolyte of Comparative Example 1 was tested. The specific testing method is: a half-cell is prepared using the solid electrolyte materials of Examples 1-7 and Comparative Example 1 and a metallic lithium negative electrode, and the AC impedance of the half-cell is tested. The body resistance R in the AC impedance spectrum, the area A of the electrolyte film facing the contact electrode, and the thickness d of the electrolyte film are taken. The ionic conductivity σ of the electrolyte film can be obtained by the following formula:
[0125] The test results are shown in Table 1.
[0126] Cycle capacity test: A lithium battery charge and discharge tester was used to perform a cycle test on the lithium-ion all-solid-state battery. The voltage range was 3.0V-4.2V, the charge and discharge rate was 0.1C, constant current charging was 30min, and constant current discharging was 30min alternately cycled. The cycle capacity was tested for 100 cycles. The test results are detailed in Table 1.
[0127] Table 1 is a summary of the test data of the ionic conductivity and the cycle capacity of the batteries of Examples 1-7 of the present invention and Comparative Example 1 after 100 cycles at 0.1C:
[0128]
[0129] From the data comparison in Table 1, it can be seen that the ionic conductivity of the materials prepared in Examples 1-7 is higher than that in Comparative Example 1, especially the Li 10.1 Ge 0.9 Lu 0.1 P2S 12 The ionic conductivity is the highest, reaching 3.75×10 -2 S / cm, this is because in Example 5, Lu replaces Ge to generate vacancies, and lithium ions are compensated, while in the increased lattice Li + While increasing the concentration and fluidity of Lu, the ion radius of Lu is lower than that of other rare earth elements. Doping with the tetravalent invariant element Lu with a smaller radius can increase the volume of tetrahedral vacancies and reduce the activation energy of lithium ion diffusion in tetrahedral vacancies, thereby increasing the mobility of lithium ions and the lithium ion conductivity, thereby increasing the cycle capacity.
[0130] The embodiment of the present invention provides a rare earth element doped lithium germanium phosphorus sulfur solid electrolyte and its preparation method and application. Lithium sulfide Li2S, germanium sulfide GeS2, sulfide of rare earth element M, and phosphorus pentoxide P2S5 are synthesized by a high temperature solid phase method, wherein the lithium sulfide Li2S is in an excess of 5%-10%; the valence state of the rare earth element is positive trivalent, and the positive tetravalent germanium element in the lithium germanium phosphorus sulfur solid electrolyte is doped to replace part of the lithium germanium phosphorus sulfur solid electrolyte, and the vacancies in the lattice of the lithium germanium phosphorus sulfur solid electrolyte are compensated by lithium ions. The optimal lithium ion concentration is adjusted by substitution doping of unequal cations, which can significantly increase the number of lithium ion transfers, change the distribution of lithium ions, increase the lithium ion hopping rate, reduce the grain boundary resistance, and thus improve the ionic conductivity of the lithium germanium phosphorus sulfur solid electrolyte; the rare earth element doped lithium germanium phosphorus sulfur solid electrolyte provided by the embodiment of the present invention is applied to an all-solid-state lithium secondary battery to improve the cycle capacity.
[0131] A rare earth element-doped lithium germanium phosphorus-sulfur solid electrolyte provided in an embodiment of the present invention reduces the manufacturing cost of the electrolyte by selecting rare earth resources with abundant reserves and relatively low prices to dope and replace part of the germanium element; a rare earth element-doped lithium germanium phosphorus-sulfur solid electrolyte preparation method provided in an embodiment of the present invention is environmentally friendly, energy-saving, and suitable for large-scale production.
[0132] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A rare earth element doped lithium germanium phosphorus sulfur solid electrolyte, characterized in that: The chemical formula of the rare earth element doped lithium germanium phosphorus sulfur solid electrolyte is Li 10+x Ge 1-x M x P2S 12 , wherein 0.01≤x<1, M includes: one or more rare earth elements selected from lanthanum La, cerium Ce, praseodymium Pr, neodymium Nd, promethium Pm, samarium Sm, europium Eu, gadolinium Gd, terbium Tb, dysprosium Dy, holmium Ho, erbium Er, thulium Tm, ytterbium Yb, lutetium Lu, scandium Sc, and yttrium Y; The rare earth element has a positive trivalent valence, and is doped to replace a portion of the positive tetravalent Ge element in the lithium germanium phosphorus sulfur solid electrolyte. The vacancies in the crystal lattice of the lithium germanium phosphorus sulfur solid electrolyte are replaced by Li + to make compensation; The rare earth element doped lithium germanium phosphorus sulfur solid electrolyte is prepared by synthesizing lithium sulfide Li2S, germanium sulfide GeS2, sulfide of the rare earth element M, and phosphorus pentoxide P2S5, wherein the addition amount of the lithium sulfide Li2S is 5%-10% excess according to the stoichiometric ratio.
2. A method for preparing the rare earth element doped lithium germanium phosphorus sulfur solid electrolyte according to claim 1, characterized in that: The preparation method comprises: Step S1, weighing raw materials according to a stoichiometric ratio: lithium sulfide Li2S, germanium sulfide GeS2, sulfide of rare earth element M and phosphorus pentoxide P2S5; placing the raw materials in a grinder, adding a first dispersant under a protective atmosphere, grinding and mixing them evenly to obtain a mixed material; Step S2, placing the mixed material in a ball mill, performing the first ball milling under a protective atmosphere, and placing the material in a vacuum drying oven for drying to evaporate the dispersant to obtain a powder; Step S3, loading the powder into a corundum crucible, placing the crucible in a vacuum atmosphere furnace, evacuating the vacuum, and then filling the crucible with an inert gas for pre-sintering to obtain a pre-sintered bulk material; Step S4, placing the pre-sintered bulk material in a ball mill, adding a second dispersant, and performing a second ball milling to obtain a precursor material; Step S5, placing the precursor material in a vacuum atmosphere furnace, evacuating the vacuum and then filling it with an inert gas to perform a high-temperature solid-phase reaction, naturally cooling to room temperature after the reaction is completed, and performing a third ball milling after the material is discharged to obtain a rare earth element-doped lithium germanium phosphorus sulfur solid electrolyte; The chemical formula of the rare earth element doped lithium germanium phosphorus sulfur solid electrolyte is Li 10+x Ge 1-x M x P2S 12 , wherein 0.01≤x<1, M includes: one or more rare earth elements selected from lanthanum La, cerium Ce, praseodymium Pr, neodymium Nd, promethium Pm, samarium Sm, europium Eu, gadolinium Gd, terbium Tb, dysprosium Dy, holmium Ho, erbium Er, thulium Tm, ytterbium Yb, lutetium Lu, scandium Sc, and yttrium Y; The amount of lithium sulfide Li2S added is 5%-10% excess according to the stoichiometric ratio.
3. The preparation method according to claim 2, characterized in that: The sulfide of the rare earth element M includes one or more of the rare earth element sulfides containing lanthanum La, cerium Ce, praseodymium Pr, neodymium Nd, promethium Pm, samarium Sm, europium Eu, gadolinium Gd, terbium Tb, dysprosium Dy, holmium Ho, erbium Er, thulium Tm, ytterbium Yb, lutetium Lu, scandium Sc, and yttrium Y; The first dispersant includes: one or more of deionized water, anhydrous ethanol, propanol, and ethylene glycol; the mass ratio of the first dispersant to the total mass of the raw materials is 1:[0.8-1.5]; The second dispersant includes: one or more of deionized water, anhydrous ethanol, propanol, and ethylene glycol; the mass ratio of the second dispersant to the pre-burned block material is 1:[0.8-1.5].
4. The preparation method according to claim 2, characterized in that: The protective atmosphere is nitrogen atmosphere and / or argon atmosphere; The inert gases are nitrogen and / or argon.
5. The preparation method according to claim 2, characterized in that: The first ball milling and the second ball milling are both wet milling processes, the ball milling speed is 550 rpm-750 rpm, and the ball milling time is 10 hours-20 hours; The third ball milling is a dry milling process, the ball milling speed is 600 rpm, and the ball milling time is 2 hours.
6. The preparation method according to claim 2, characterized in that: The drying temperature is 80°C-200°C, and the drying time is 2 hours-6 hours; The temperature of the pre-sintering treatment is 200° C.-300° C., and the time of the pre-sintering treatment is 10 hours-15 hours.
7. The preparation method according to claim 2, characterized in that: The temperature of the high-temperature solid-phase reaction is 500° C.-600° C., the heating rate is 2° C. / min-4° C. / min, and the time of the high-temperature solid-phase reaction is 10 hours-20 hours.
8. A lithium ion battery, characterized in that: The lithium-ion battery comprises the rare earth element-doped lithium-germanium-phosphorus-sulfur solid electrolyte as claimed in claim 1.
Citation Information
Patent Citations
All-solid state electrolyte material and preparation method thereof as well as all solid-state lithium secondary battery
CN108832172A
Lanthanum-doped lithium germanium phosphorus sulfur solid electrolyte as well as preparation method and application thereof
CN115224354A